The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1371/journal.pone.0013550
|View full text |Cite
|
Sign up to set email alerts
|

Room for Improvement in Conducting and Reporting Non-Inferiority Randomized Controlled Trials on Drugs: A Systematic Review

Abstract: BackgroundA non-inferiority (NI) trial is intended to show that the effect of a new treatment is not worse than the comparator. We conducted a review to identify how NI trials were conducted and reported, and whether the standard requirements from the guidelines were followed.Methodology and Principal FindingsFrom 300 randomly selected articles on NI trials registered in PubMed at 5 February 2009, we included 227 NI articles that referred to 232 trials. We excluded studies on bioequivalence, trials on healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 14 publications
5
71
1
1
Order By: Relevance
“…This is in line with the range of margins that were defined by expert opinions in previous reviews (25 to 75%) [9, 11, 22, 23]. Our findings also highlight the issue of not providing enough details on the method that was used to define the margin.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with the range of margins that were defined by expert opinions in previous reviews (25 to 75%) [9, 11, 22, 23]. Our findings also highlight the issue of not providing enough details on the method that was used to define the margin.…”
Section: Discussionsupporting
confidence: 90%
“…In the evaluation of non-inferiority trials by Wangge et al . [14] there one third of trials were also reported as open label. In their review they pointed out that this was not consistent with the guidelines, which recommend blinding of any randomised trial whenever possible [4].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a number of topics assessed in our review do not apply, or are not directly comparable with the situation in bioequivalence trials. Furthermore, other similar studies [10,13,14] also excluded bioequivalence trials, and it was one of the aims of our work to compare our results with others.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous review, we found that most non-inferiority trials were financed by the pharmaceutical industry (73.7%). [12] In this study, we identified questions on non-inferiority trials that were posed by applicants for scientific advice in Europe in 2008 and 2009, and the responses given by the EMA. Our analysis of the questions about non-inferiority trials posed by applicants in scientific advice dialogues with the EMA could identify any complex issues in the regulation of non-inferiority trials that may benefit from more explicit regulatory guidance.…”
Section: Introductionmentioning
confidence: 99%